Erbium doped ZBLAN fiber laser operating in the visible - feasibility study - Komorowski, Paweł; Anders, Krzysztof; Zdulska, Urszula; Piramidowicz, Ryszard (Photonics Letters of Poland, 2017)
This work is focused on developing all-fiber green laser in hybrid geometry, based on combination of Er:ZBLAN active fiber and silica fiber-based passive components of optical resonator and deploying Fiber Bragg Gratings (FBGs) as highly selective mirrors for green spectral range. The scope of work covers fundamental spectroscopic characterization of Er:ZBLAN samples, determination of key spectroscopic parameters, modelling the lasing properties and lasing experiments in different pumping geometries. Full Text: PDF References W.P. Risk, T.R. Gosnell, A.V. Nurmikko, "Compact blue-green lasers", Cambridge University Press. (2003) CrossRef J.Y. Allain, M. Monerie, and H. Poignant, "Tunable green upconversion erbium fibre laser", Electronics Lett., 28 (1992) 111-113 CrossRef Z . Luo, Q. Ruan, M. Zhong, Y. Cheng, R. Yang, B. Xu, H. Xu, Z. Cai, "Compact self-Q-switched green upconversion Er:ZBLAN all-fiber laser operating at 543.4 nm", Optics Lett. 41 (2016) 2258-2261 CrossRef D. E. McCumber, "Einstein relations connecting broadband emission and absorption spectra", Physical Review 136 (1964) 954-957 CrossRef